MENGEMBANGKAN KREATIVITAS DAN KEMAMPUAN BERPIKIR LOGIS PADA ANAK USIA DINI - Soegeng Santoso (Perspektif Ilmu Pendidikan, 2006)
Each child has different and specific competence which needs to be developed as early as possible. The development of such competence depends on several factors such genetic inheritance and environment. The child’s creativity will develop well if it is maintained and motivated by outside stimuli. This can be done through creative learning. Logical thinking can be developed through mathematical intelligence. Creativity and logical thinking can be developed through fun learning activities